Group portraits of (Czechoslovakian) soldiers in the Spanish Civil War. Copy of picture from Vojenský Historický Archiv
Group portraits of (Czechoslovakian) soldiers in the Spanish Civil War. Copy of picture from Vojenský Historický Archiv.